Knowledge of the Problem and Intention to Act on Student Environmentally Responsible Behavior - Firmansyah, Fahmie; Kamil, Mustofa; Suherman, Suherman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
The issue of national environmental damage itself is a lively issue discussed starting from damage caused by water, water, soil pollution, climate change or global warming, depletion of natural resources, extinction of biodiversity, deforestation, oceans acidification, abrasion, and so on. One of the factors causing damage to the environment is human action which exploits nature excessively and lacks concern for the environment. The purpose of this study was to see the effect of knowledge about environmental issues and the intentions to act on students ' environmental responsibility behavior. Research researchers used a causal survey method by using a type of quantitative research with path analysis techniques (path analysis). Based on the research results, there is a direct effect of knowledge of issue on the intentions to act with a score of 0.587. Second, there is a direct effect of intention to act on environmentally responsible behavior with a score of 0.735. Third, there is a direct effect of knowledge of issue on the attitude of environmental responsibility with a score of 0.603. Finally, there is an indirect effect of knowledge of issue on environmentally responsible behavior through intention to act with a score of 0.431.